H-2-linked regulation of xenotropic murine leukemia virus expression. - Yetter, R A (1983)
A high proportion of lymphocytes from F/St mice produce infectious xenotropic murine leukemia virus (X-MuLV) and express high levels of cell surface antigens, termed XenCSA, related to the major glycoprotein of X-MuLV. In crosses of F/St with AKR, the high-virus phenotype of F/St was found to be recessive and was shown to be governed by a single locus, Cxv-1, less than 2 centimorgans from H-2K. The close association of Cxv-1 with the H-2 complex was confirmed by the observation that B10.F mice, congeneic for the H-2 region of F/St, expressed high levels of infectious X-MuLV and XenCSA, whereas C57BL/10 mice and other C57BL/10 H-2 congeneic strains did not. Studies of hybrid mice homozygous for Cxv-1s, but segregating for a chromosome 1 X-MuLV induction locus (V locus) of F/St, demonstrated that the high-virus phenotype of F/St was dependent on the interaction between Cxv-1 and the chromosome 1 V locus.